The Concept of Character Learning: A Comparative Study of Al-Ghazali and Thomas Lickona’s Perspectives - Syamsul Huda; Muhamim Sarifudin; Munifah Munifah; Anis Humaidi; Saifullah Idris; Mawardi Mawardi (DAYAH: Journal of Islamic Education, 2022)
The main goal in character education is to achieve noble character to create a harmonious human life, helping each other, being fair, and having a balanced relationship in social life. Because of that, instilling character in students is fundamental so that when they grow up, they can become the next generation of solid character. This study uses library research that compares the concept of learning the character of al-Ghazali and Thomas Lickona. The research method carried out in this study was carried out with several steps, such as collecting qualitative data based on reputable data sources and analyzing data to obtain final results. The study results show that Al-Ghazali's educational method is a traditional nuanced method of "lecture and uswah hasanah". Furthermore, Al-Ghazali's educational materials are all forms of teachings contained in the Islamic religion. More clearly and concretely, the concept of education initiated by Al-Ghazali contains two elements: transcendence (rububiyyah: divine) and humanization. Meanwhile, the concept of character learning initiated by Thomas Lickona formulates character learning that involves all components in the education process, both family, school, and community. In addition, the character learning process, according to Thomas Lickona is an effort that involves three aspects of intelligence, including cognitive through moral knowing, affective through moral feeling, and psychomotor through moral acting as follows: The purpose of character learning is to help students become intelligent and good in manners.